The Molecular Basis of Gender Variations in Mortality Rates Associated With the Novel Coronavirus (COVID-19) Outbreak - Hachim, Ibrahim Y.; Hachim, Mahmood Y.; Talaat, Iman Mamdouh; López-Ozuna, Vanessa M.; Saheb Sharif-Askari, Narjes; Al Heialy, Saba; Halwani, Rabih; Hamid, Qutayba (Frontiers in Molecular Biosciences, 2021)
Since the outbreak of the novel coronavirus disease (COVID-19) at the end of 2019, the clinical presentation of the disease showed a great heterogeneity with a diverse impact between different subpopulations. Emerging evidence from different parts of the world showed that male patients are usually had longer mean disease course as well as worse outcome compared to female patients. A better understanding of the molecular mechanisms behind this difference might be a fundamental step for more effective and personalized response to this disease outbreak. For that reason, here we try to investigate the molecular basis of the gender variations in mortality rates related to COVID-19 infection. To achieve this, we used publicly available lung transcriptomic data from 141 females and compare it to 286 male lung tissues. After excluding Y specific genes, our results showed a shortlist of 73 genes that are differentially expressed between the two groups. Further analysis using pathway enrichment analysis revealed downregulation of a group of genes that are involved in the regulation of hydrolase activity including (CHM, DDX3X, FGFR3, SFRP2, and NLRP2) in males lung compared to females. This pathway is believed to be essential for lung immune response and antimicrobial activity in the lung tissues. In contrast, our results showed an upregulation of angiotensin II receptor type 1 (AGTR1), a member of the renin-angiotensin system (RAS) that plays a role in angiotensin-converting enzyme 2 (ACE2) activity modulation, in male lungs compared to females. Finally, our results also showed a differential expression of genes that are involved in the immune response including the NLRP2 and PTGDR2 between lung tissues from both genders, further supporting the notion of the sex-based immunological differences. Taken together, our results provide an initial evidence of the molecular mechanisms that might be involved in the differential outcomes observed between both genders during the COVID-19 outbreak. This might be essential for the discovery of new targets and more precise therapeutic options to treat COVID-19 patients from different clinical and epidemiological characteristics with the aim of improving their outcome.